Rhetoric in history: Nikephoros Gregoras and his portrayal of Andronikos II palaiologos - Pavlović Bojana (Zbornik Radova Vizantološkog Instituta)
The paper examines the rhetorical tools employed by the Byzantine historian Nikephoros Gregoras to create a complex and multilayered portrait of the emperor Andronikos II. Writing the historical books dealing with the emperor’s reign spanned several years, in which significant changes occurred within the Empire. The author begins his portrait of Andronikos II at the court of Andronikos III and concludes it, presumably, after the latter’s demise. This approach enabled the author to highlight the discrepancies in the portrayal of Andronikos II. The article compares Andronikos II with his father and brother in the initial section, before contrasting him with his grandson, Andronikos III, in the subsequent part. The primary issues addressed in this paper pertain to the chronology of Gregoras’s historical work and the censorship practices prevalent during the Palaiologan era.